Objective outcome and quality‐of‐life assessment in women with repeat incontinence surgery. Issue 6 (27th September 2016) - Ulrich, Daniela; Bjelic‐Radisic, Vesna; Grabner, Katrin; Avian, Alexander; Trutnovsky, Gerda; Tamussino, Karl; Aigmüller, Thomas
Abstract : Aims: To evaluate subjective and objective outcome after repeat surgery for stress urinary incontinence (SUI). Methods: Patients who underwent a midurethral tape after failed Burch colposuspension or failed midurethal tape between 1999 and 2014 were invited for follow‐up. Urogynecological examination and urodynamics was performed, and objective cure was defined as a negative cough stress test; subjective cure was defined as negotiation of SUI symptoms. Quality‐of‐life (QoL), sexual health, and subjective success was assessed with the King's Health Questionnaire, Incontinence Outcome Questionnaire, Female Sexual Function Index, and the Patient Global Impression of Improvement (PGI‐I) score. Results: Overall 52 women underwent repeat incontinence surgery. Out of the 44 women still alive, 33 (75%) were available for follow‐up. All 33 women completed the questionnaires; 23 women (70%) attended the clinic and also had an urogynecological examination. At a median follow‐up of 11 years, subjective cure was 67% (22/33), objective cure was 65% (16/23), and subjective success according to PGI‐I was 78% (18/23), with no significant differences between groups. No erosions of suture or tape material into the bladder, urethra, or vagina were seen. Two women had received a third anti‐incontinence operation with TVT after failed tape after failed Burch, and were continent at follow‐up. Two women with tape after colposuspension required division of the tape and both were continent at the time of follow‐up. With regard to QoL and sexual health, no significant differences were seen for most domains. Conclusions: Midurethral tapes are an option for women with recurrent SUI after previous colposuspension or midurethral tape.